2018
DOI: 10.1101/341503
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamics of cortical GABA in human motor learning

Abstract: The ability to learn novel motor skills is both a central part of our daily lives and can provide a model for rehabilitation after a stroke. However, there are still fundamental gaps in our understanding of the physiological mechanisms that underpin human motor plasticity. The acquisition of new motor skills is dependent on changes in local circuitry within the primary motor cortex (M1). This reorganisation has been hypothesised to be facilitated by a decrease in local inhibition via modulation of the neurotra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
42
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 40 publications
(61 reference statements)
10
42
2
Order By: Relevance
“…This possibility is in agreement with the biphasic model of skill learning described by Vinogradov et al (2012). In this model, Phase 1 is characterized by rapid improvements in behavior, which have been associated with downregulation of cortical inhibition in animal models (Sale et al, 2010) and in humans (Kolasinski et al, 2019). In light of previous findings that transient specific manipulation of PV+ interneurons affects the initial rate of learning (Letzkus et al, 2011;Donato et al, 2013;Wolff et al, 2014), our results add to the mounting evidence indicating that suppression of PV+ cells is necessary for the initiation of learning (Hu et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…This possibility is in agreement with the biphasic model of skill learning described by Vinogradov et al (2012). In this model, Phase 1 is characterized by rapid improvements in behavior, which have been associated with downregulation of cortical inhibition in animal models (Sale et al, 2010) and in humans (Kolasinski et al, 2019). In light of previous findings that transient specific manipulation of PV+ interneurons affects the initial rate of learning (Letzkus et al, 2011;Donato et al, 2013;Wolff et al, 2014), our results add to the mounting evidence indicating that suppression of PV+ cells is necessary for the initiation of learning (Hu et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…No relationship between changes in Glx and task performance post-intervention nor between GABA or Glx and change in PPT score 6 weeks after stimulation and training was observed. These results are in accordance with adult studies that report no significant relationship between change in motor skill and concentration of Glx in the motor cortex contralateral to the hand executing the task (33). However, adult studies have reported a relationship between task improvement and GABA changes in the tDCS targeted cortex (i.e.…”
Section: Relationship Between Changes In Metabolites and Changes In Msupporting
confidence: 91%
“…Additionally, this is the first-time metabolites have been measured in a control population after a multiday protocol with a followup assessment. Previous studies in adults have illustrated that GABA decreases (33,46) and glutamate increases (47), with skill acquisition and improved function in the region responsible for the skill execution, the M1. It has been suggested that tDCS facilitates changes in GABA and glutamate to augment learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has become apparent that tDCS applied to M1 affects motor learning, possibly by altering GABA concentrations. In healthy participants, GABA concentration decreases in the M1 during motor learning (Kolasinski et al, 2018), and anodal tDCS can enhance cortical excitability while decreasing GABA concentration in M1 (Stagg et al, 2011a). Furthermore, Stagg et al (2011a) found a positive correlation between the magnitude of the tDCS-induced GABA decrease in M1 and the degree of motor learning.…”
mentioning
confidence: 90%